First-principle calculations of structural, electronic and magnetic investigations of Mn2RuGe1-xSnx quaternary Heusler alloys - Semari, F.; Dahmane, Fethallah; Baki, N.; Al-Douri, Yarub; Akbudak, Salih; Ugur, Gokay; Ugur, Sule; Bouhemadou, Abdelmadjid; Khenata, Rabah; Voon, Chun Hong (Elsevier, 2018)
First-principles calculations were used to calculate the structural, electronic and half-metallic ferromagnetism of Mn2RuGe1-xSnx (x = 0, 0.25, 0.50, 0.75, 1) Heusler alloys. The Hg2CuTi-type structure is found to be energetic more than Cu2MnAl-type structure for both Mn2RuGe and Mn2RuSn compounds. The calculated lattice constants for Mn2RuGe and Mn2RuSn are 5.91 Å and 6.17 Å, respectively. The electronic band structures and density of states of Mn2RuGe show a half metallic character with total magnetic moments, 2 μB per formula unit that are in good agreement with Slater-Pauling rule with indirect band gap, 0.31 eV along the direction Γ –X. It is observed that the total magnetic moment per cell increases as Sn concentration increases in the Heusler alloys.